Case Report: Functional Outcome of COVID-19 Subjects With Myasthenia Gravis and Critical Illness Polyneuropathy - Intiso, Domenico; Centra, Antonello Marco; Amoruso, Luigi; Gravina, Michele; Rienzo, Filomena Di (Frontiers in Neurology, 2022)
Background COVID-19 disease can affect subjects suffering from myasthenia gravis (MG) and worsen its clinical course, leading to intensive care unit (ICU) admission. Critically ill subjects can develop a neuromuscular complication defined ICU-acquired weakness (ICUAW). This disorder has also been detected in ICU subjects with COVID-19, but the association of MG and ICUAW has never been described in critically ill patients. We describe the case and the functional outcome of a COVID-19 patient suffering from MG who developed critical illness polyneuropathy (CIP). Case Presentation A 66-year-old man with a history of hypertension and ocular MG had COVID-19 disease and required ICU admission. The patient underwent mechanical ventilation and tracheotomy and was treated with remdesivir and corticosteroids. Fifteen days after admission, he complained tetraparesis without ocular involvement that remained unchanged despite the increase of anticholinesterase therapy. Length of stay (LOS) in ICU was 35 days. On day 2 from admission, the patient underwent frontal muscle jitter study that confirmed MG and electroneurography (ENG) and electromyography (EMG) that showed overlapping ICUAW with electrophysiological signs characteristic of CIP. Cerebrospinal fluid (CSF) show normal pressure, cells count and protein levels (<45 mg/dL) without albumin-cytologic disassociation. The CSF/serum glucose ratio was normal. CSF culture for possible organisms, laboratory test for auto-immune disorders, panel of antiganglioside antibodies, and paraneoplastic syndrome were negative. Strength and functional outcome were tested by MRC scale, DRS Barthel scale and FIM at admission, discharge and follow-up. Muscular strength improved progressively, and MRC sum score was 50 at discharge. Anticholinesterase therapy with pyridostigmine at the dosage of 30 mg, 3 times daily, which the patient was taking before COVID-19 disease, was resumed. His motor abilities recovered, and functional evaluations showed full recovery at follow-up. Conclusion In described subject, the coexistence of both neuromuscular disorders did not affect the clinical course and the recovery, but question remain about generalization to all patients with MG. The rehabilitation interventions might have facilitated the outcome.